SPE European Formation Damage Conference &Amp; Exhibition 2013
DOI: 10.2118/165089-ms
|View full text |Cite
|
Sign up to set email alerts
|

Self-Diverting Acid for Effective Carbonate Stimulation Offshore Brazil: A Successful History

Abstract: The stimulation history in offshore Brazil is undergoing into a deep transformation. The requirements of technology, before focused on sandstone reservoirs demand, are being expanded by the need for techniques to stimulate carbonate reservoirs, specially the pre-salt carbonates. In this scenario, a self-diverting acid system based on a viscoelastic surfactant (VES) technology was introduced for carbonate reservoir stimulation. The Self-Diverting VES (SD-VES) promotes viscosity development when the acid comes i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Overall, they considered the treatments successful. Jardim Neto et al 112 reported the use of a self-diverting acid system with an internal breaker in Brazil. They reported the treatment of three oil wells in carbonate reservoirs.…”
Section: Mechanisms Of Viscosity Reductionmentioning
confidence: 99%
“…Overall, they considered the treatments successful. Jardim Neto et al 112 reported the use of a self-diverting acid system with an internal breaker in Brazil. They reported the treatment of three oil wells in carbonate reservoirs.…”
Section: Mechanisms Of Viscosity Reductionmentioning
confidence: 99%
“…However, the application of variable viscosity acid is limited because the crosslinking agent currently used is mainly a metal crosslinking agent and metal ions are more harmful to the reservoir [ 10 , 11 ]. The viscoelastic surfactant variable viscosity acid (VES) obtained by the association between surfactants can also improve the effect of acid fracturing [ 12 , 13 ]. The viscoelastic surfactant variable viscosity acid (VES) obtained by the association between surfactants can also improve the effect of acid fracturing.…”
Section: Introductionmentioning
confidence: 99%